GENERASI MUDA MILLENIAL DALAM PERSPEKTIF ISLAM - Irfan Musadat (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
The purpose of this study is to enlighten readers, especially young people, about the millennial generation in Islamic perspective and strive to be able to make a positive contribution to the younger generation so that they are inspired to always act positively, constructively and not fall into destructive associations. In this paper the author tries to describe qualitatively about the Millennial generation in the view of Islam through the library research approach by collecting data through various kinds of literature and documents in the form of personal notes, books, journals and others related to the discussion of Millennial generation in the view of Islam. Millennials, also known as generation Y, are the demographic group after generation X. The term comes from millennials coined by two American historians and writers, William Strauss and Neil Howe in several of his books Millennial generation or generation Y is also known as generation me or echo boomers. Syekh Musthafa al Ghulayaini in his' idhoh he said